The Professionalism Matrix: A Framework to Analyze Professional & Unprofessional Behaviors - Lawrence Loo; Van Geslani; Samuel Baz; Leah Tudtud-Hans (Association of American Medical Colleges, 2014)
Abstract Introduction As residency programs integrate ACGME core competencies into their curricula, they must continually seek to find avenues of instruction that both teach and evaluate these competencies. This workshop introduces the Professionalism Matrix, a tool that can help learners evaluate complex professionalism scenarios using a graphical format. The goal of the workshop is to help learners see professionalism as a competency that is habitual, contextual, and developmental by framing it in the context of ACGME and ABIM milestones. It also helps learners not only see which behaviors are unprofessional, but gives them a framework as to why those behaviors are unprofessional. Methods Included in this workshop is a background PowerPoint presentation, the Professionalism Matrix, a detailed workshop plan, and several scenarios that can be used for discussion. Slides can be adapted to fit the specific needs of the particular learning environment. We have applied the Professionalism Matrix in several interactive conferences. The learner audiences have included house staff in our internal medicine residency, a chief residents' conference that included all departmental specialties, and a university-wide faculty development session that had representatives from the schools of medicine, nursing, and allied health professions. The workshop has also been presented nationally at the Alliance for Academic Internal Medicine's Academic Internal Medicine Week in 2013. Results Conference evaluations have been uniformly positive indicating that the Professionalism Matrix facilitated a systems-based practice approach to the interpretation of potentially unprofessional conduct. The small-and large-group discussions highlighted the importance of considering the micro-, meso-, and macro-levels that may influence an individual's reasoning and motivation for seemingly unprofessional actions. Outside of the conference, we have also begun to use the Matrix in our monthly residency evaluation committee meeting when evaluating unprofessional behavior among our residents. Further, faculty have now begun to use the Matrix as a framework to discuss interdepartmental unprofessional behavior (i.e., between internal medicine residents and emergency medicine residents). Discussion The integration of the ACGME's definition of professionalism, the incorporation of ABIM/ACGME-related milestones, and their being cross-referenced with a system-based framework to analyze issues contextually makes the Professionalism Matrix a novel educational tool that could readily be adopted by other institutions.